Quadruple H-bonding cross-linked supramolecular polymeric materials as substrates for stretchable, antitearing, and self-healable thin film electrodes - Yan, Xuzhou (2020)
Herein, we report a de novo chemical design of supramolecular polymer materials (SPMs-1–3) by condensation polymerization, consisting of (i) soft polymeric chains (polytetramethylene glycol and tetraethylene glycol) and (ii) strong and reversible quadruple H-bonding cross-linkers (from 0 to 30 mol %). The former contributes to the formation of the soft domain of the SPMs, and the latter furnishes the SPMs with desirable mechanical properties, thereby producing soft, stretchable, yet tough elastomers. The resulting SPM-2 was observed to be highly stretchable (up to 17 000% strain), tough (fracture energy ∼30 000 J/m2), and self-healing, which are highly desirable properties and are superior to previously reported elastomers and tough hydrogels. Furthermore, a gold, thin film electrode deposited on this SPM substrate retains its conductivity and combines high stretchability (∼400%), fracture/notch insensitivity, self-healing, and good interfacial adhesion with the gold film. Again, these properties are all highly complementary to commonly used polydimethylsiloxane-based thin film metal electrodes. Last, we proceed to demonstrate the practical utility of our fabricated electrode via both in vivo and in vitro measurements of electromyography signals. This fundamental understanding obtained from the investigation of these SPMs will facilitate the progress of intelligent soft materials and flexible electronics.